Changes in mean sea level around Great Britain over the past 200 years. (March 2021) - Hogarth, P.; Pugh, D.T.; Hughes, C.W.; Williams, S.D.P.
Highlights: This paper systematically integrates a large amount of historical sea level data into a consistent and improved sea level record for Great Britain over the last 200 years. Much of this data is from previously unpublished sources. The density of new data allows an independent sea level curve to be derived which confirms the sea level rise and increase in rate of rise between the 19th and 20th Centuries observed in previous work, and in other studies from Northern Europe. The length of the composite record has been considerably extended, with much of the new data being from the first half of the 19th Century. The importance of data archaeology (and the maintenance of national archives) is demonstrated. A framework is provided so that any new data that is recovered in future can be added, and similar records can be constructed where data can be recovered elsewhere in the world. Abstract: We systematically assimilate a wide range of historical sea level data from around the coast of Great Britain, much of it previously unpublished, into a single comprehensive framework. We show that this greatly increased dataset allows the construction of a robust and extended Mean Sea Level curve for Great Britain covering a period of more than two centuries, and confirms that the 19th century trend was much weaker than that in the 20th century and beyond. As well as attempting to maximise the amount of newly recovered sea level observations, we have also recovered the levelling metadata necessary to connect this 19th and early 20th century data with modern records. We adjust this data for known sources of variability and estimate overall uncertainties over the entire period. Data are processed in 36 regional clusters, before recombining to compute national statistics. We investigate the advantages of extending and adjusting the time series on sea level rise trends and low order variability. Confidence limits are improved by better than 60%. The weighted linear trend since 1900 for the fully adjusted data points from all clusters when averaged annually and adjusted for Glacial Isostatic Adjustment is 2.12 mm/year ± 0.02 mm/year (1-sigma). The much lower trend estimated for the 19th Century alone is 0.24 ± 0.12 mm/yr. There is an acceleration of 0.012 mm/yr 2  ± 0.003 mm/yr 2 in the rate of rise over the period 1813 to 2018. These trends are quite sensitive to the GIA correction used, but their differences and accelerations are not.